Detection of PLZF- RARa fusion in patients with Acute Promyelocytic Leukemia - M Araghi (پیاورد سلامت, 2008)
Background and Aim: Acute promyelocytic leukemia (APL) is associated with the t(1517) ,fusing promyelocytic leukemia (PML) and retinoic acid receptor-a (RARa) genes. This disease is uniquely sensitive to treatment with all-trans retinoic acid (ATRA) and highly responsive to conventional chemotherapy. The t(1117)(q23q21) abnormality associated with a PLZF-RARa rearrangement is the commonest of the alternative translocations accounting for less than 1% APL. Blasts from PLZF-RARa cases have been found to be resistant to the differentiating effects of retinoids. In this study we aimed to determine the PLZF-RARa and fusion genes in patients with APL morphology who referred to Hematology-Oncology and BMT research center, Tehran Shariaty Hospital in 2006. Materials & Methods: Peripheral blood and/or bone marrow samples were taken from 200 patients with APL morphology and 200 patients with other subtypes of AML. The mono-nuclear cells were enriched by centrifugation over a ficoll-isopaque gradient. RNA extracted by Trizol or TriReagent and then reverse transcribed to cDNA using random primers. PCR performed using specific primers for each fusion. PCR products electerophoresed on a 2% agarose gel containing 0.05% ethidiume bromide. Results: In 2 (1%) patients with APL-morphology the RT-PCR analysis showed PLZF-RARa fusion transcripts. Conclusion: It can be concluded that RT-PCR is a rapid and sensitive method for detection of abnormal fusion genes in leukemia and allows the definition of a correct strategy for treatment and subsequent minimal residual disease monitoring